Nodding syndrome: a concise review. Issue 1 (22nd April 2020) - Olum, Sam; Scolding, Peter; Hardy, Charlotte; Obol, James; Scolding, Neil J
Abstract: Nodding syndrome is an uncommon epileptic disorder of childhood onset, which appears to occur exclusively in clusters in sub-Saharan Africa. It was first reported in the 1960s, in what is now southern Tanzania, then in Liberia, and later in South Sudan and northern Uganda, with both epidemic and endemic patterns described. The cause remains unknown. Here we describe the background and development of descriptions of the disorder, review its clinical features and summarize current theories and studies concerning its cause, outlining the principal remaining research questions relating to this highly unusual disease. Abstract : Nodding syndrome is an uncommon, acquired, childhood-onset neurological disorder comprising epilepsy usually combined with cognitive and occasionally other systemic problems. It appears to occur in clusters exclusively in sub-Saharan Africa, in both epidemic and endemic patterns. Here we review its history and clinical features and current hypothesis concerning its cause. Graphical Abstract: